A new microstructure‐based multiaxial fatigue life prediction model for A319 casting alloys. Issue 9 (24th May 2021) - Zhou, Zhiqiang; Liu, Xiaoshan; He, Guoqiu; Ge, Bin; Le, Peiwen; Pan, Jiaqi; Huang, Ziao; Li, Jingquan; Wang, Qigui
Abstract: This paper describes a microstructure‐based multiaxial nonproportional fatigue life prediction model applied to A319 alloy. The materials made with different casting cooling rates and Sr modification are characterized and quantified in terms of secondary dendrite arm spacing, size, and aspect ratio of eutectic Si particles. Multiaxial nonproportional fatigue tests have been performed on six groups of A319 alloys to systematically analyze the effect of microstructure and loading path on the fatigue properties of Al–Si cast alloy. The first part of the paper is focused on microstructure quantitative characterization to determine the influence of different casting conditions, followed by stress response behavior and fatigue fracture analysis. Finally, a new multiaxial fatigue life prediction model for Al–Si alloy is proposed, for which 56% of the data points fall in the bound lines of factor of 2 and 83% of the data points fall in the bound lines of factor of 3.